Uncovering the complex relationships among distributed leadership, departmental teacher leadership, and professional learning community in Chinese schools - Xin Zheng; Chenxi Jiang; Chenlu Liu (Future in Educational Research)
AbstractProfessional learning community (PLC) has been widely recognized as an effective approach for promoting both student learning and teacher development. Existing research on PLC mainly focuses on the school‐level, and less attention has been given to the departmental‐level PLC. Given the complex nature of school structures, departmental PLC may be influenced by multiple leadership factors, including principal and teacher leadership (TL). This study investigates how the distributed leadership (DL) of principals and TL influence departmental PLC and individual teacher self‐efficacy. Drawing on a sample of 602 teachers in China, the results showed that TL had a direct impact on teacher self‐efficacy and had an indirect effect through PLC. Additionally, the DL of principals indirectly affects individual teachers through TL and PLC. The results indicate the complex leadership structure in schools with various levels of leadership exerting distinct influences on teachers and departments. It highlights the roles of principal leadership and TL in facilitating PLC and teacher development. Implications for school leadership and PLC development are discussed.